Modelos político-criminais e presunção de inocência: a Defensoria Pública da Paraíba no duplo grau de jurisdição - Morais, Anderson Medeiros de (2020)
The work presents an interdisciplinary approach regarding the performance of the Public Defender of Paraíba in the double degree of jurisdiction with the instances of the Paraíba judiciary, dealing with the matter of precautionary arrests. The research aims to find answers to identify how the Public Defender's Office carries out its activities at the state level. It is a documentary research to be carried out with an emphasis on the area of human rights, focused on scientific discussions from the legal sciences, criminology, criminal policy, sociology, philosophy and theory of law. In view of the high number of people serving deprivation of liberty, which in the state of Paraíba, as well as in the national average, represents about 40% of the prison population, the notorious impacts of super incarceration and the recent debates on the possibility of imprisonment after the second instance judgment, there is a need for an in-depth investigation of the proposed theme. With this, it is intended to establish some conclusions about the activities performed by the Public Defender of Paraíba to provide protection to the constitutional guarantee of the presumption of innocence of part of the population of Paraiba considered to be underfunded. To this end, it was initially planned to contextualize the political-criminological aspects resulting from liberal, authoritarian and totalitarian models. Then, through a doctrinal discussion, from the perspective of Ferrajoli and Bobbio's juspositivist approach, the main topics about guaranteeing the presumption of innocence and its connection with the high rate of precautionary prisons in the Brazilian criminal process will be studied. Then, an attempt will be made to formulate a concept on the Public Defender's Office, as an institution responsible for providing full and free legal assistance, and, on its functions, as an institution essential to the jurisdictional function of the State, in particular on its performance in court. in the double degree of jurisdiction. Finally, an analysis will be made of the numbers of habeas corpus filed by the Public Defender of Paraíba in order to revoke preventive prisons in order to be able to conclude more precisely about the efficiency of the institution's performance in relation to the matter that was defined by the present study. Through a methodological construction oriented towards the preparation of an essentially documentary research, it is intended to carry out a descriptive and analytical analysis so that the phenomenon that appears as an investigated object can be described. Thus, it is intended to reach conclusions regarding the performance of the Public Defender's Office of the State of Paraíba as responsible for providing full and free legal assistance at the state level and whose primary function is to defend fundamental rights of the most needy population in the state, in particular, from the enjoyment to the presumption of innocence on the part of those assisted who are in the course of judicial proceedings of a criminal nature.